Does the South African timeshare market provide financial institutions with an opportunity to enter the industry to extend its product range thereby increasing its loan book? - Mania, Enrico Vittorio (My University, 2009)
The research question enquires if the timeshare market provides financial institutions with opportunities to adapt the timeshare market offering as an extension of their product range thereby growing the loan portfolio which it can hold as an income producing annuity or securitise this debt to realise profits. The timeshare market has grown substantially from modest beginnings in Europe in the early sixties to a world wide multi billion US dollar industry by the turn of the century. Despite a tarnished image and an industry associated with hard sell techniques, it continues to enjoy acceptance amongst consumers as a way of ensuring future holidays by fixing the cost, up front. The research showed that timeshare which is an entrenched concept is viewed as a consumer product and not as an investment. International literature highlights various risks associated with timeshare as well as the high cost of sales, high maintenance costs [levies] and exit costs. The literature is unanimous that if these costs could be reduced there would be more investment in timeshare thereby attracting a wider audience. The research also indicates that a business needs to conduct value chain analysis not only to look at its costs and performance in each value creating activity but also on ways to improve thereupon. Although the managing of core processes is vital to a company’s survival it also needs to scan the market environment to identify competitors. A company should have a competitive intelligence system that allows it to recognise the threat of new technologies and / or emerging products. Integration (backward or forward) is a grand strategy available to a business enabling a company greater control of the value / supply chain. The research report has tried to quantify the opportunities available to financial institutions to implement backward vertical integration in a market that they have steered clear from due to the “high risk” tag it carries. Due to the lack of up to date information the research report is mainly qualitative. It should be treated as a pilot study, highlighting what is of importance and which areas are to be treated with care when entering the timeshare market.